STUDENT LEARNING MOTIVATION IN THE FIELD OF PHYSICS METHODOLOGICAL METHODS OF FORMATION - Eshbayeva, M. (SCIENCE and SOCIETY, 2026)
The article examines methodological techniques aimed at increasing students’ interest in studying physics. Psychological and pedagogical foundations of motivation are analyzed, along with specific techniques and forms of work used at different stages of the lesson. Special attention is given to problem-based learning, interactive methods, project activities, and modern technologies. Examples of successful practices and conditions for effective implementation of methodological techniques are presented. The work focuses on developing sustainable learning motivation and improving the quality of physics teaching in modern schools.
Keywords: methodological techniques; student interest; motivation; physics education; problem-based learning; interactive methods; project activities; pedagogy